Demographics, Risk Factors, and Negative Historical Events of Inpatients with a History of Sexual Abuse - Laser, Julie Anne; Petersen, Granger; Stephens, Haily; DeRito, David; Boeckel, Jennifer (Advances in Social Sciences Research Journal, 2019)
The purpose of this research is to better understand how those who have experienced a mental hospital inpatient stay are influenced by a history of sexual abuse. Both risk factors and negative historical events were investigated between those who had a sexual abuse history in an inpatient hospital and those in the inpatient hospital who did not have a sexual abuse history. It was found that sexual abuse exerts a profound influence on those in the mental hospital. For example, a sexual abuse history for inpatient men was twice the national average and over 4x the national average for inpatientwomen. Additionally, many of the risk factors and negative events were significantly different between the two inpatient sub-samples. It was also found that a sexual abuse history was related to more hospital stays and longer overall time in the hospital. It is hoped that this research can make a major contribution to improving trauma informed care with this population so that a history of sexual abuse does not undermine their well-being throughout their life span.